Biomedical Image Mapping: Issues And Challenges - Nurzi Juana Mohd Zaizi; Albert Burger (International Journal of Computer and Information Technology (IJCIT), 2024)
Biomedical imaging has become an essential tool in both basic research and the clinical sciences. Significant advances in imaging modalities such as computed tomography (CT) or magnetic resonance imaging (MRI) in recent years have contributed to a substantial increase in the quantity and quality of such images. Being able to integrate and compare such image-based data is useful for epidemiological studies, educational uses, monitoring the clinical progress of a patient or translational science purposes. The work presented in this paper uses examples from biomedical atlases. This paper discusses the need for biomedical image data integration, the shortcomings of existing solutions and proposes the opportunity to build a new technique.